2017
DOI: 10.1186/s12864-016-3388-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune adaptation to chronic intense exercise training: new microarray evidence

Abstract: BackgroundEndurance exercise training, especially the high-intensity training, exhibits a strong influence on the immune system. However, the mechanisms underpinning the immune-regulatory effect of exercise remain unclear. Consequently, we chose to investigate the alterations in the transcriptional profile of blood leukocytes in young endurance athletes as compared with healthy sedentary controls, using Affymetrix human gene 1.1 ST array.ResultsGroup differences in the transcriptome were analyzed using Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 39 publications
3
42
0
1
Order By: Relevance
“…Previous studies examined the impact of physical activity or dietary interventions on DNA methylation in blood or circulating blood lymphocytes, but few examined an intervention incorporating both health behaviors [6][7][8][9][10]41]. For example, Nakajima et al demonstrated that moderate-intensity walking for ≥ 26 min/day, 2 days/week among 436 healthy adults was associated with ASC methylation [35], which controls IL-1β and IL-18 inflammatory cytokine expression [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies examined the impact of physical activity or dietary interventions on DNA methylation in blood or circulating blood lymphocytes, but few examined an intervention incorporating both health behaviors [6][7][8][9][10]41]. For example, Nakajima et al demonstrated that moderate-intensity walking for ≥ 26 min/day, 2 days/week among 436 healthy adults was associated with ASC methylation [35], which controls IL-1β and IL-18 inflammatory cytokine expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the Cardiovascular Health Study, higher physical activity was associated with an anti-inflammatory phenotype via TNF hypermethylation and IL-10 hypomethylation [12]. Moreover, among adult endurance athletes and sedentary controls (n = 24), Liu et al found 72 differentially expressed genes in blood leukocytes with genes in inflammation and oxidative stress pathways [10]. Chilton et al found that treadmill running for 30 min was associated with higher TERT and SIRT6 gene expression in leukocytes, which regulate telomeres [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the current findings, no significant alterations in blood immunoglobulin concentrations were reported in male distance runners after a 12.5-km run (18). Evidences suggest that regular exercise training down regulates biological processes of inflammation in athletes (19). It seems that lack of IgA levels change in army rangers after simulated operation stems from inflammatory processes down regulation due to regular army ranger training program.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, such research has rapidly increased since the completion of the genome maps of humans and several important model animals. Previous genome studies in sports medicine have mostly focused on the bodily and cellular responses to exercise.…”
mentioning
confidence: 99%